2014
DOI: 10.1080/03055698.2014.930337
|View full text |Cite
|
Sign up to set email alerts
|

The school playground experience: opportunities and challenges for children and school staff

Abstract: The school playground experience is an inevitable part of school life for primary school children. For most children, the experience is a positive and enjoyable one that contributes to their physical and social well-being and has been associated with enhanced attention and learning in the classroom. For some children, however, the playground can be a frightening and dangerous place in which aggressive behaviour and bullying can be experienced and/or witnessed. The recognition of this fact has, in some cases, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…The least physically active children’s temporal perspective showed that recess time was perceived as speeded up when they were enjoying themselves and slowed down when they were feeling bored. In line with our study, a study by Mulryan-Kyne showed that the majority of children typically experienced recess as a fast going enjoyable time [ 69 ]. In another study, children mentioned being able to enjoy games and physical exercise as positive features of recess [ 70 ], similar to most of the high activity children in our study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The least physically active children’s temporal perspective showed that recess time was perceived as speeded up when they were enjoying themselves and slowed down when they were feeling bored. In line with our study, a study by Mulryan-Kyne showed that the majority of children typically experienced recess as a fast going enjoyable time [ 69 ]. In another study, children mentioned being able to enjoy games and physical exercise as positive features of recess [ 70 ], similar to most of the high activity children in our study.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with Blatchford et al who found that recess first and foremost was a social event [ 71 ]. A study found that, for many children, school was the only setting in which opportunities for learning to negotiate and manage conflicts as well as form new friendships with a wide range of peers from their own and other classes existed [ 69 ]. However, in our study most of the least physically active children were close friends and peer relations had been established in kindergarten.…”
Section: Discussionmentioning
confidence: 99%
“…Although it would be ideal to have a playmate who demonstrated positive play skills and the emotional maturity to be flexible throughout the sessions, real life play situations do not exclusively involve considerate playmates and positive play outcomes (Mulryan‐Kyne, ). Both children in the dyad will benefit from developing their skills in repairing play situations with each other, with and without adult support (Mulryan‐Kyne ). We believe that the improved ability to repair play situations will support generalisation of skills to other peers and environments after practicing in a safe, naturalistic setting created in the clinic (Wilkes‐Gillan et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The positive trend in the play skills of the playmates is worth exploring further. Although it would be ideal to have a playmate who demonstrated positive play skills and the emotional maturity to be flexible throughout the sessions, real life play situations do not exclusively involve considerate playmates and positive play outcomes (Mulryan‐Kyne, ). Both children in the dyad will benefit from developing their skills in repairing play situations with each other, with and without adult support (Mulryan‐Kyne ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation